Evaluation of lambung mangkurat university student academic portal using user experience questionnaire (UEQ) - Sari, Yuslena; Novitasari, Novitasari; Pratiwi, Hani (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2021)
The student academic portal is one of the Academic Information Systems at The University of Lambung Mangkurat (ULM). The ULM student academic portal can only be accessed by the ULM students. It can be used for academic guidance, managing student study plans, printing test cards, filling out questionnaires, and viewing exam results (assessment). However, since its release in 2016, there has been no publication regarding evaluations on the website-based ULM student academic portal. Evaluation is one of the stages in the Software Development Life Cycle (SDLC). This stage allows the user to assess the system. This study aims to evaluate the academic portal of the ULM students. Evaluation is carried out to determine the user's evaluation of the existing system. The evaluation method used is the User Experience Questionnaire (UEQ). With this method, users can assess the ULM Student Academic Portal from various aspects: Novelty, Stimulation, Dependability, Efficiency, Perspicuity, and Attractiveness. The results of this study indicate that the Perspicuity aspect gets a high score while Novelty gets a low score.